2014
DOI: 10.1152/ajpcell.00167.2013
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic mapping of proteins released during necrosis and apoptosis from cultured neonatal cardiac myocytes

Abstract: Cardiac injury induces myocyte apoptosis and necrosis, resulting in the secretion and/or release of intracellular proteins. Currently, myocardial injury can be detected by analysis of a limited number of biomarkers in blood or coronary artery perfusate. However, the complete proteomic signature of protein release from necrotic cardiac myocytes is unknown. Therefore, we undertook a proteomic-based study of proteins released from cultured neonatal rat cardiac myocytes in response to H2O2 (necrosis) or staurospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In the last decade, there have been several efforts to dissect out cardiac mRNA and proteome in a wide array of cardiovascular diseases (McGregor and Dunn, 2006) using different animal models or plasma samples collected from human patients (Seenarain et al, 2010; Haas et al, 2011; Silbiger et al, 2011; Drastichova et al, 2012; Chowdhury et al, 2013; Marshall et al, 2014; Petriz and Franco, 2014). While novel biomarkers were identified from some of these studies (Haas et al, 2011; Silbiger et al, 2011; Chowdhury et al, 2013), authors reported general alterations in the cardiac transcriptome and proteome profile that suggested changes in Ca2+ handling proteins (Seenarain et al, 2010), energy metabolism proteins (Jin et al, 2006; Meng et al, 2009), and mediators of apoptotic signaling (Drastichova et al, 2012; Marshall et al, 2014; Petriz and Franco, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there have been several efforts to dissect out cardiac mRNA and proteome in a wide array of cardiovascular diseases (McGregor and Dunn, 2006) using different animal models or plasma samples collected from human patients (Seenarain et al, 2010; Haas et al, 2011; Silbiger et al, 2011; Drastichova et al, 2012; Chowdhury et al, 2013; Marshall et al, 2014; Petriz and Franco, 2014). While novel biomarkers were identified from some of these studies (Haas et al, 2011; Silbiger et al, 2011; Chowdhury et al, 2013), authors reported general alterations in the cardiac transcriptome and proteome profile that suggested changes in Ca2+ handling proteins (Seenarain et al, 2010), energy metabolism proteins (Jin et al, 2006; Meng et al, 2009), and mediators of apoptotic signaling (Drastichova et al, 2012; Marshall et al, 2014; Petriz and Franco, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…7 The development of more sensitive troponin assays is another example of how proteomics has enabled the development of improved diagnostic methods, 8 with high-sensitivity troponin assays permitting earlier diagnosis of acute coronary syndromes. 9,10 MS was an integral part of the harmonization of cardiac troponin I assays, which was accomplished by development of a human cardiac standard to calibrate troponin assays.…”
Section: The Foundation Of Proteomicsmentioning
confidence: 99%
“…Clinically useful biomarkers can include circulating proteins that have been secreted or leaked directly into the plasma from resident cells (e.g., myocytes) following diseases or injuries (15), and are thus spatially uncoupled from the transcript change at the tissue of origin. The tissues of origin of circulating proteins may be unknown, inaccessible, or invasive to procure, making it impractical to hunt for these potential biomarkers via transcript measurements, instead of protein measurements.…”
Section: Overviewmentioning
confidence: 99%